Predictors of Impaired Survival in Subjects With Long-Term Oxygen Therapy. - Rantala, Heidi A.; Leivo-Korpela, Sirpa; Lehtimäki, Lauri; Lehto, Juho T. (Respiratory Care, 2019)
BACKGROUND: The need for long-term oxygen therapy (LTOT) is usually a sign of advanced disease, which could trigger advance care planning. However, LTOT is used in patients with different characteristics and multiple diagnoses beyond COPD. We studied the factors associated with survival in an unselected sample of subjects who started LTOT. METHODS: We conducted a retrospective study that included 195 subjects for whom LTOT was initiated in Tampere University Hospital from January 1, 2012, to December 31, 2015, and followed up until December 31, 2017. RESULTS: The most frequent diseases that caused the need for LTOT were COPD and interstitial lung diseases. Most of the subjects (69%) died during the study period; the median survival time was 2.2 y. The subjects with interstitial lung disease as a primary disease for LTOT had a shorter survival time (median 0.9 y) compared with those with COPD (median 2.4 y, P < .001). Survival was shorter in the subjects ages >75 y (median 1.4 y) compared with those who were ages ≤75 y (median 2.8 y, P = .001) and also in those who required help with daily activities (median 1.2 y) compared with those who did not (median 3.3 y, P < .001). In multivariate analysis, a diagnosis of interstitial lung disease (hazard ratio 2.1, 95% CI 1.4-3.2), Charlson comorbidity index (hazard ratio 1.26, 95% CI 1.11-1.43), and required help in activities of daily living (hazard ratio 2.1, 95% CI 1.4-3.1) were associated with impaired survival. CONCLUSIONS: The survival of the subjects who started LTOT varied greatly. The subjects with interstitial lung disease and those who required assistance with activities of daily living were at risk of dying in ~1 y, which suggested that advance care planning should be directed especially to these patients.